2020
DOI: 10.1055/s-0040-1714039
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydroxyapatite and Ellagic Acid in the Osteogenesis

Abstract: Objective Ellagic acid (EA), a phenolic antioxidant, has benefits in bone health and wound healing. The combination of EA and hydroxyapatite (HA) (EA-HA) is expected to increase osteogenesis. The aim of this study was to analyze osteogenesis after application of EA-HA according to the number of osteoblasts and osteoclasts in the bone and the expression of the receptor activator of nuclear factor kappa- ligand (RANKL), osteoprotegerin (OPG), and osteocalcin (OCN) protein. Materials and Methods Thirty Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Inhibition of this inflammatory process will lead to an increase in the process of tissue regeneration. In the previous study, ellagic acid is able to increase the number of osteoblast cells, the expression of OCN and OPG in the bone regeneration process (Wardhana et al, 2020). Ellagic acid has also shown that this material is not toxic to normal cells of the body, such as fibroblast (Nirwana et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Inhibition of this inflammatory process will lead to an increase in the process of tissue regeneration. In the previous study, ellagic acid is able to increase the number of osteoblast cells, the expression of OCN and OPG in the bone regeneration process (Wardhana et al, 2020). Ellagic acid has also shown that this material is not toxic to normal cells of the body, such as fibroblast (Nirwana et al, 2021).…”
Section: Discussionmentioning
confidence: 88%
“…The antiinflammatory properties works by inhibit the pro-inflammatory cytokines that affected on inhibition of bone formation or osteogenesis (Al-obaidi et al, 2014). The osteogenesis stimulation by ellagic acid involve the increased the osteocalcin (OCN), osteoprotegerin (OPG) and stimulate the osteoblast during bone regeneration (Wardhana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…31 Wardhana AS, et al use ellagic-hydroxyapatite acid to promotes osteogenesis in bone defects by increasing the amounts of osteoblasts and therefore the expression of osteoprotegerin and osteocalcin. 32 HA is a scaffold that can bond with MMPs and reduce its activities in vitro. Secretion and MMP activities are regulated well, and in normal tissues, MMP is expressed on a fundamental level.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that free oxygen radicals are produced in the inflammatory phase by phagocytic cells on the bone surface. In the study of Wardhana et al [ 29 ], an increase in osteoclast formation and bone resorption was observed, which is thought to prevent free radicals from remineralizating in the bone defect and tooth eruption.…”
Section: Discussionmentioning
confidence: 99%